The Oxford Encyclopedia of the Military in Politics - Thompson, William R.; Nassif, Hicham Bou (New York: Oxford University Press, 2022)
"This encyclopedia provides the definitive resource for exploring the role that military personnel and organizations have played in politics. Many of the articles examine how the military has been involved in politics in specific states. Other articles link the country-specific accounts to broader questions concerning the military in politics, such as what factors encourage military coups, what are the consequences of military rule, how do military personnel vote, and whether military expenditures boost economic growth. No other work has examined the relationships between governments and their military with such breadth. As a result, the Oxford Encyclopedia of the Military in Politics is a necessary resource for students, specialists, and scholars"--
Includes bibliographical references and index.
Keywords: Civil-military relations -- Encyclopedias; Armed Forces -- Political activity -- Encyclopedias; Comparative government -- Encyclopedias